2023
DOI: 10.1128/jmbe.00053-23
|View full text |Cite
|
Sign up to set email alerts
|

Preprint Peer Review Enhances Undergraduate Biology Students' Disciplinary Literacy and Sense of Belonging in STEM

Abstract: Education

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Engaging the high school student in authentic science writing and publication, while relatively limited, is a growing experience. We anticipate that such student engagement not only serves to elevate their science literacy (Golden, 2023; Fankhauser, et al 2021; Mattison, et al 2022) but could also facilitate their development of identity and belonging in science (Carlone & Johnson, 2007; Deemer et al, 2022; Florence & Yore, 2004; Kim, et al 2023; Otto et al, 2023; Trujillo & Tanner, 2017). Thus, as these types of opportunities become more widespread, it’s important to understand how we’re mentoring our students to become familiar with the genre norms and the role of this type of communication within the process of science.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging the high school student in authentic science writing and publication, while relatively limited, is a growing experience. We anticipate that such student engagement not only serves to elevate their science literacy (Golden, 2023; Fankhauser, et al 2021; Mattison, et al 2022) but could also facilitate their development of identity and belonging in science (Carlone & Johnson, 2007; Deemer et al, 2022; Florence & Yore, 2004; Kim, et al 2023; Otto et al, 2023; Trujillo & Tanner, 2017). Thus, as these types of opportunities become more widespread, it’s important to understand how we’re mentoring our students to become familiar with the genre norms and the role of this type of communication within the process of science.…”
Section: Discussionmentioning
confidence: 99%
“…For example, participation in science literature can increase student understanding of science inquiry and concepts (Golden, 2023). At the undergraduate level, students who participate in authentic peer-reviews of preprint articles report greater STEM identity (Otto et al, 2023); and similarly at the graduate level, students who engage in the disciplinary literacy practices of writing a research paper and serving as a peer-reviewer report higher identity factors, indicating that students view participation in these practices as part of their scientific identity (Florence & Yore, 2004). Authentically engaging in the research process may increase students' confidence in scientific abilities which further strengthens their sense of identity in the STEM field (Trujillo & Tanner, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Together with other promising examples in biology (Otto et al, 2023), we hope that other disciplines may take this as inspiration for developing similar pedagogical tools and instruments according to their specific needs and requirements.…”
Section: Limitationsmentioning
confidence: 96%
“…In addition, previous initiatives were not explicitly embedded into a structured training programme at the undergraduate level. We know of only one exploratory study that reported on successful inclusion of peer review within an undergraduate biology curriculum for 19 students (Otto et al, 2023). The structure of undergraduate programmes can present considerable challenges for teaching peer review because accredited undergraduate degrees are required to deliver specific modules aligned with their programme structures, leaving limited opportunity to add an additional module focused exclusively on peer reviewing.…”
Section: Introductionmentioning
confidence: 99%
“…Instructors who cannot offer a complete course on peer review may still consider incorporating the module into existing science courses as a way to develop students' disciplinary literacy, scientific identity, and sense of belonging in STEM. In essence, the development of scientific literacy is carried out through peer review of scientific manuscripts (Otto et al, 2023).…”
Section: January 2024mentioning
confidence: 99%